1972
DOI: 10.1111/j.2044-8295.1972.tb02083.x
|View full text |Cite
|
Sign up to set email alerts
|

Peak Shift, Behavioural Contrast and Stimulus Generalization as Related to Personality and Development in Children

Abstract: Fourteen children, aged 7–11 years, were selected from an initial sample of 190 to give a range of scores on the JEPI. They were also evaluated by a Teacher's Rating Scale for neuroticism. The children were trained in a discrimination learning task which yielded measures of peak shift, behavioural contrast and stimulus generalization. Peak shift and behavioural contrast were positively correlated. Neuroticism was positively correlated with both one measure of peak shift and stimulus generalization. Extraversio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

1972
1972
1996
1996

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 77 publications
(24 citation statements)
references
References 5 publications
3
21
0
Order By: Relevance
“…Although such differences are inevitable when an experiment involves the establishment of asymptotic response levels for individual subjects, it is necessaiy to test the possibility that this variable contributed to individual differences in the various behavioural measures. Analysis of the present data confirmed Nicholson and Gray's (1972) finding that length of pre-training was unrelated to the incidence of behavioural contrast, peak shift, mean shift or any of the other behavioural measures studied.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Although such differences are inevitable when an experiment involves the establishment of asymptotic response levels for individual subjects, it is necessaiy to test the possibility that this variable contributed to individual differences in the various behavioural measures. Analysis of the present data confirmed Nicholson and Gray's (1972) finding that length of pre-training was unrelated to the incidence of behavioural contrast, peak shift, mean shift or any of the other behavioural measures studied.…”
Section: Discussionsupporting
confidence: 92%
“…Apart from the behavioural measures, the only other variable in Table 2 which distinguishes between the two groups is chronological age. Nicholson and Gray (1972) confirmed that the frustration effects declined with advancing age amongst the Normal children. The fact that the Maladjusted boys are significantly older than the Normals (for CA, I = 9-07, p < 0-001) makes their greater susceptibility to frustration the more striking.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…When time appears to pass slowly, more impulsive behaviour and a higher rate of discounting are expected. Second, extraverts are characterized by a greater susceptibility to rewards (Eysenck, 1967;Eysenck and Gudjonsson, 1989;Gupta and Nagpal, 1978;Nicolson and Gray, 1972;Seunath, 1975). It well might be that to extraverts, an immediate reward is a stronger incentive than it is for introverts, thereby leading to more impulsive behaviour and a higher rate of temporal discounting.…”
Section: Extraversionmentioning
confidence: 98%
“…An individual is less likely to wait for a delayed reward (thus showing a steep rate of temporal discounting) when the reward constitutes a strong temptation (Mischel et al, 1989). Eysenck (1967;Eysenck and Gudjonsson, 1989) claims that extraverts are characterized by a higher susceptibility to rewards than are introverts (see also Gupta and Nagpal, 1978;Nicolson and Gray, 1972;Seunath, 1975). According to Gray (1970;1981), the impulsivity dimension is based on differences in susceptibility to rewards, with high-impulsive individuals being more susceptible to signals of rewards (and of no punishment) than low-impulsive individuals.…”
Section: Introductionmentioning
confidence: 96%